2016
DOI: 10.1177/1468087416675708
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterization of particulate matter emitted by lean-burn gasoline direct injection engine

Abstract: This study presents detailed characterization of the chemical and physical properties of particulate matter emitted by a 2.0-L BMW lean-burn turbocharged gasoline direct injection engine operated under a number of combustion strategies that include lean homogeneous, lean stratified, stoichiometric, and fuel-rich conditions. We characterized particulate matter number concentrations, size distributions, and the size, mass, compositions, and effective density of fractal and compact individual exhaust particles. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Engine studies have also shown high EC percentages (70-93%) [98,110], but other studies have found much lower percentages (15-35%) [111,112]. With dedicated engine studies it was also shown that idle or fuel cut conditions can increase the volatile part [110] and that the EC fraction is higher under lean stratified conditions (80%) compared to stoichiometric (60%) [113].…”
Section: Chemical Compositionmentioning
confidence: 97%
“…Engine studies have also shown high EC percentages (70-93%) [98,110], but other studies have found much lower percentages (15-35%) [111,112]. With dedicated engine studies it was also shown that idle or fuel cut conditions can increase the volatile part [110] and that the EC fraction is higher under lean stratified conditions (80%) compared to stoichiometric (60%) [113].…”
Section: Chemical Compositionmentioning
confidence: 97%
“…It is generally held that solid accumulation mode particles, those with mobility diameter ( D p ) approximately equal to 30–500 nm, mostly consist of carbonaceous soot. Conversely, solid nucleation mode ( D p ∼ 3–30 nm) particles do not consist of nucleated organics, but rather of ash metals originating from the engine lubricating oil 2426 and potentially of primary soot particles. 25 As given in Figure 3(a), the PSD for stoichiometric engine conditions with the most advanced injection timing settings resulted in a large concentration in the accumulation mode size range and the latest injection led to large concentrations in the ash nucleation mode size range.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, solid nucleation mode ( D p ∼ 3–30 nm) particles do not consist of nucleated organics, but rather of ash metals originating from the engine lubricating oil 2426 and potentially of primary soot particles. 25 As given in Figure 3(a), the PSD for stoichiometric engine conditions with the most advanced injection timing settings resulted in a large concentration in the accumulation mode size range and the latest injection led to large concentrations in the ash nucleation mode size range. Although size distribution and mass concentration between these two cases were very different, the total PN concentrations were on the same order of magnitude (10 12 ) as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…PM mass from a GDI engine appears to have a large BC component (Maricq, Szente, and Jahr 2012). Depending on engine operating conditions, particles may consist of various amounts of amorphous carbon, semivolatile organic compounds (SVOCs), and ash contents (Karjalainen et al 2014;Zelenyuk et al 2016). The majority of PNs are smaller than 100 nm (Amanatidis et al 2017;Chen et al 2017;Hassaneen, Samuel, and Whelan 2011;Myung, Ko, and Park 2014;Tan et al 2016;Yamada, Funato, and Sakurai 2015).…”
Section: The Human Health Perspective: Comments From Rashid Shaikhmentioning
confidence: 99%